High-performance conductive concrete with low doping amount of carbon fibers and preparation method of high-performance conductive concrete

By using low-dollar carbon fiber and steel fiber in conductive concrete, combined with hydroxyethyl cellulose and tributyl phosphate, the problems of high cost of conductive materials and reduced mechanical properties are solved, and conductive concrete with low resistivity and high mechanical properties are achieved, reducing production costs.

CN119707408APending Publication Date: 2025-03-28INNER MONGOLIA UNIVERSITY

Patent Information

Application Number
CN202510244352.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing conductive concrete has high cost of conductive materials under large amounts, which makes it impossible to promote and use on a large scale. Excessive graphite dosage will reduce the mechanical properties of the concrete.

Method used

Low-dollar carbon fiber and steel fiber are used as conductive materials, and hydroxyethyl cellulose is used as dispersant and tributyl phosphate is used as defoaming agent to significantly improve the dispersion of carbon fiber and the conductivity of concrete.

Benefits of technology

It realizes the low resistivity and high mechanical properties of conductive concrete under low doping conditions, reduces production costs and improves the conductive properties, making it suitable for large-scale promotion and use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707408A_ABST
    Figure CN119707408A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, in particular to high-performance conductive concrete with low doping amount of carbon fibers and a preparation method of the high-performance conductive concrete. The conductive concrete is prepared from the following raw materials in parts by weight: 66 to 68 parts of cement, 24 to 25 parts of fly ash, 10 to 12 parts of silica fume, 16.8 to 20.5 parts of mixing water, 70.2 to 72.8 parts of river sand, 0.035 to 0.437 parts of short carbon fibers, 7.8 to 11.7 parts of steel fibers, 0.15 to 0.2 part of hydroxyethyl cellulose, 0.315 to 0.42 part of a de-foaming agent, 1.255 to 1.575 parts of a water reducing agent and 35 to 40 parts of water. The steel fibers serve as a main frame of a conductive network in the concrete and are preliminarily lapped to form the conductive network, the frame lapped by the steel fibers is subsequently filled with the carbon fibers, a more complete conductive network is formed, low resistivity of the conductive concrete is guaranteed, and high mechanical performance of the conductive concrete is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a high-performance conductive concrete with a low amount of carbon fiber added and a preparation method thereof. Background Art

[0002] Conductive concrete is a multiphase composite material usually made of cementitious materials, aggregates, conductive fillers, water and admixtures. Conductive concrete has many applications, usually in structural health monitoring, traffic detection, energy conversion / storage, road deicing and snow melting, building heating, cathodic protection, electrostatic protection, etc. Compared with conductive concrete, ordinary concrete has a higher resistivity, which is 105-107 at room temperature. , between a poor conductor and an insulator. Currently, commonly used conductive materials include graphite, nano carbon black, carbon nanotubes, steel fiber, carbon fiber, graphene, etc., but due to the high cost of conductive materials at large dosages and high production costs, they cannot be promoted and used on a large scale. Graphite, nano carbon black, carbon nanotubes, etc. are inorganic materials commonly used as conductive fillers. Graphite is easier to obtain and relatively economical than nano carbon black and carbon nanotubes, but graphite needs to be added in a large amount to make the concrete conductive. However, a large amount of graphite will greatly reduce the mechanical properties of the concrete, and nano carbon black and carbon nanotubes are too little to show conductivity, and increasing the dosage cannot meet the economic requirements.

[0003] Steel fiber has the characteristics of improving the compression, tension, bending and other mechanical properties of concrete. At the same time, as a metal material, it can also play its conductive function in concrete. In addition, steel fiber also has very strong corrosion resistance to sulfate ions and chloride ions, can fully adapt to the internal environment of concrete, can be used continuously in a high temperature aerobic environment of 600℃, and has good heat resistance.

[0004] Carbon fiber has high conductivity, which makes it have extremely low resistivity. Carbon fiber also has good chemical stability and can resist corrosion from acids, alkalis, salts, etc. It can still maintain its conductivity and mechanical properties in harsh environments. It can adapt to the internal environment of concrete and can be used as a composite material with metal materials to meet various needs. It also has high strength and high modulus, and its density is relatively low, generally 1.7-2.0g / cm 3 It can reduce the weight of concrete and reduce the transportation price, but the price of carbon fiber is relatively high and it is not suitable to add a large amount to prepare conductive concrete. Therefore, in order to reduce the production cost of conductive concrete, it is necessary to develop a preparation method of low-dosage carbon fiber high-performance conductive concrete. Summary of the invention

[0005] In view of the defects of the prior art, the purpose of the present invention is to provide a high-performance conductive concrete with a low amount of carbon fiber and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0006] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a high-performance conductive concrete with a low amount of carbon fiber, wherein the conductive concrete comprises the following raw materials in parts by weight: 66-68 parts of cement, 24-25 parts of fly ash, 10-12 parts of silica fume, 16.8-20.5 parts of mixing water, 70.2-72.8 parts of river sand, 0.035-0.437 parts of short-cut carbon fiber, 7.8-11.7 parts of steel fiber, 0.15-0.2 parts of hydroxyethyl cellulose, 0.315-0.42 parts of defoaming agent, 1.255-1.575 parts of water reducer and 35-40 parts of water; The steel fiber is also impregnated, and the specific impregnation method is: The steel fiber and the impregnation liquid were ultrasonically impregnated at a weight ratio of 3:5, and after the impregnation was completed, the steel fiber was filtered and dried; The preparation method of the infiltration liquid is as follows: 2-5 parts of 5% by mass sodium silicate solution, 1-3 parts of silicon carbide whiskers, 3-5 parts of graphene and 3-5 parts of 4% by mass dopamine hydrochloride solution are fully mixed to obtain the infiltration liquid.

[0007] Compared with other types of dispersants and defoamers, the present invention selects hydroxyethyl cellulose as a dispersant and tributyl phosphate as a defoamer, which can significantly disperse the bundled carbon fibers, improve the uniformity of the carbon fibers in the concrete soil, significantly reduce the resistivity of the conductive concrete, and improve its conductivity, so as to form a more complete conductive path inside the concrete, and further improve the mechanical properties and electrical properties of the conductive concrete.

[0008] Preferably, the type of cement is P·O42.5 ordinary Portland cement; the fly ash is secondary fly ash; the water reducer is polycarboxylic acid high-efficiency water reducer; the defoamer is organic phosphorus defoamer tributyl phosphate; and the water is ordinary domestic water.

[0009] Preferably, the river sand is standard river sand with a fineness modulus of 2.3-3.0, and the chopped carbon fiber has a tensile strength of 4900 MPa, a tensile modulus of 230000 MPa, a density of 1.75 g / cm³, a fiber diameter of 0.007 mm, a bulk density of 0.4 g / cm³, and a resistivity of 1.0-1.6 × 10 -1 ; The steel fiber is copper-plated microfilament steel fiber, with a length of 10-13mm, a diameter of 0.12mm, and a density of 7800kg / m 3 。

[0010] Too much cementitious material such as cement, fly ash, and silica fume will lead to incomplete cement hydration, thereby reducing its mechanical properties such as compressive strength and flexural strength. If too little cementitious material is added, it will make concrete difficult to form. Too much mixing water will lead to excessive water-cement ratio of concrete, resulting in water bleeding. Too little addition will lead to poor fluidity of concrete, which cannot meet the requirements of work performance. Small amount of river sand will lead to reduced matrix pore structure, which will not only reduce mechanical properties, but also make it impossible to form a complete conductive path, so that its resistivity increases. In addition, the water reducer used in the present invention is a polycarboxylic acid, a pure water-reducing water reducer with a water reduction rate of up to 27%. If the water reducer is used in too much amount, it will lead to water bleeding, the test piece cannot be formed, and the final setting time is extended. If the water reducer is used in too little amount, the slurry is too viscous and normal work performance cannot be guaranteed. Correspondingly, too much steel fiber and carbon fiber will lead to concrete viscosity and cannot be formed normally. If the amount is too little, it is impossible to take into account both mechanical and electrical properties. The present invention controls the dosage of cement, fly ash, silica fume, carbon fiber, steel fiber, water, water reducing agent, defoaming agent and dispersant within the above range, so that the two conductive phases of steel fiber and carbon fiber can form a complete conductive path inside the concrete, while meeting the conductivity of the concrete and significantly enhancing the mechanical properties.

[0011] Preferably, the ultrasonic power of the ultrasonic infiltration treatment is 400 W, and the ultrasonic treatment is performed for 1 hour.

[0012] The present invention also provides a method for preparing high-performance conductive concrete with low carbon fiber content, comprising the following steps: Step (1), pour cement, fly ash and silica fume into a mixer in sequence, and stir and mix them evenly to obtain a mixed dry material A; Step (2), pouring 60 wt% of the total required amount of water and a water reducing agent into a mixer, stirring and mixing to obtain a mixture B; Step (3) dispersing and dissolving the hydroxyethyl fiber with 40 wt% of water in a total required amount, and stirring with a glass rod to obtain a hydroxyethyl cellulose dispersion, and then pouring the chopped carbon fiber into the dispersion, and stirring with a glass rod until the carbon fiber is free of agglomeration, to obtain a carbon fiber dispersion; Step (4) adding the carbon fiber dispersion to the mixture B, and stirring and mixing to obtain a mixture C; Step (5) adding defoamer, river sand and steel fiber to mixture C in sequence and stirring and mixing to obtain conductive concrete slurry; Step (6) pouring the obtained slurry into a mold, vibrating it sufficiently, and placing it in a standard curing room for curing. After the curing is completed, high-performance conductive concrete with a low carbon fiber content can be obtained.

[0013] Preferably, the stirring rate in step (1) is 62.5 r / min and the stirring time is 2 min; The stirring rate in step (2) is 62.5 r / min and the stirring time is 3 min; The stirring rate in step (4) is 62.5r / min and the stirring time is 4min; The stirring rate in step (5) is 62.5r / min and the stirring time is 5min; In step (3), a glass rod is used to manually stir for 1 minute to obtain a hydroxyethyl cellulose dispersion, and after adding carbon fiber, a glass rod is used to manually stir for 1 minute to obtain a carbon fiber dispersion.

[0014] Preferably, in step (6), the conductive concrete slurry is poured into the mold in two times, and is vibrated after each pouring, with the total vibration time being no less than 1 minute; and the curing conditions in the standard curing room are: the temperature is controlled at 20±2°C, and the humidity is greater than or equal to 95%.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention proposes for the first time to use chopped carbon fibers and copper-plated fine steel fibers as conductive materials. The steel fibers are used as the main framework of the conductive network inside the concrete to initially overlap into a conductive network. Subsequently, as the carbon fibers are added to fill the framework overlapped by the steel fibers, a more complete conductive network is formed, which ensures both the lower resistivity of the conductive concrete and its higher mechanical properties. The experimental results show that the concrete of the present invention has a 7d resistivity of 7. Below, the 28d resistivity is controlled at 13 , the 7d flexural strength can reach 16MPA, the 28d flexural strength can reach 23MPA, the 7d compressive strength can reach 83MPA, and the 28d compressive strength can reach 119MPA, reaching the level of ultra-high performance concrete; The resistivity of the concrete of the present invention is similar to that of CN112521076A, while the compressive strength and flexural strength are far greater than their maximum values, and the conductive material content is far greater than that of the concrete of the present invention, which ensures low cost while meeting the mechanical performance requirements; the present invention significantly reduces the production cost of conductive concrete, and effectively improves its mechanical properties and conductive properties, thereby promoting the application of conductive concrete in practical engineering; The present invention uses hydroxyethyl cellulose as a dispersant, which can change the rheological properties of the suspension and reduce the mutual adsorption between fibers, which not only increases the suspension force of the fibers so that they are not easy to sink and agglomerate, but also plays a lubricating role between the fibers, making them easier to disperse evenly, so that the short-cut carbon fibers can better exert their conductive properties; The conductive concrete of the present invention has a wide range of raw materials, requires a relatively low amount of carbon fiber, is inexpensive, and the test process is carried out at room temperature and pressure. The dispersion of the carbon fiber only requires manual stirring without the involvement of a machine, has a simple process flow, and has a low production cost. The present invention uses tributyl phosphate as a defoaming agent. Since the addition of carbon fiber and hydroxyethyl cellulose will introduce a large number of bubbles, which will reduce the mechanical properties of concrete, tributyl phosphate can effectively defoam, reduce the pores on the surface of concrete, and improve its mechanical and electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A flow chart of the preparation of high-performance conductive concrete with low carbon fiber content in Example 1 of the present invention; Figure 2 In Example 1 of the present invention, the double-electrode method uses an AC power supply to measure the resistivity of concrete. DETAILED DESCRIPTION

[0017] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] The present embodiment provides a high-performance conductive concrete with low carbon fiber content, wherein the conductive concrete comprises the following raw materials in parts by weight: 66-68 parts of cement, 24-25 parts of fly ash, 10-12 parts of silica fume, 16.8-20.5 parts of mixing water, 70.2-72.8 parts of river sand, 0.035-0.437 parts of chopped carbon fiber, 7.8-11.7 parts of steel fiber, 0.15-0.2 parts of hydroxyethyl cellulose, 0.315-0.42 parts of defoaming agent, 1.255-1.575 parts of water reducer and 35-40 parts of water.

[0019] Compared with other types of dispersants and defoamers, the present invention selects hydroxyethyl cellulose as a dispersant and tributyl phosphate as a defoamer, which can significantly disperse the bundled carbon fibers, improve the uniformity of the carbon fibers in the concrete soil, significantly reduce the resistivity of the conductive concrete, and improve its conductivity, so as to form a more complete conductive path inside the concrete, and further improve the mechanical properties and electrical properties of the conductive concrete.

[0020] The type of cement in this embodiment is P·O42.5 ordinary Portland cement; the fly ash is secondary fly ash; the water reducer is polycarboxylic acid high-efficiency water reducer; the defoamer is organic phosphorus defoamer tributyl phosphate; and the water is ordinary domestic water.

[0021] The river sand in this embodiment is standard river sand with a fineness modulus of 2.3-3.0. The chopped carbon fiber has a tensile strength of 4900 MPa, a tensile modulus of 230000 MPa, a density of 1.75 g / cm³, a fiber diameter of 0.007 mm, a bulk density of 0.4 g / cm³, and a resistivity of 1.0-1.6×10 -1 ; The steel fiber is copper-plated microfilament steel fiber, with a length of 10-13mm, a diameter of 0.12mm, and a density of 7800kg / m 3 .

[0022] Too much cementitious material such as cement, fly ash, and silica fume will lead to incomplete cement hydration, thereby reducing its mechanical properties such as compressive strength and flexural strength. If too little cementitious material is added, it will make concrete difficult to form. Too much mixing water will lead to excessive water-cement ratio of concrete, resulting in water bleeding. Too little addition will lead to poor fluidity of concrete, which cannot meet the requirements of work performance. Small amount of river sand will lead to reduced matrix pore structure, which will not only reduce mechanical properties, but also make it impossible to form a complete conductive path, so that its resistivity increases. In addition, the water reducer used in the present invention is a polycarboxylic acid, a pure water-reducing water reducer with a water reduction rate of up to 27%. If the water reducer is used in too much amount, it will lead to water bleeding, the test piece cannot be formed, and the final setting time is extended. If the water reducer is used in too little amount, the slurry is too viscous and normal work performance cannot be guaranteed. Correspondingly, too much steel fiber and carbon fiber will lead to concrete viscosity and cannot be formed normally. If the amount is too little, it is impossible to take into account both mechanical and electrical properties. The present invention controls the dosage of cement, fly ash, silica fume, carbon fiber, steel fiber, water, water reducing agent, defoaming agent and dispersant within the above range, so that the two conductive phases of steel fiber and carbon fiber can form a complete conductive path inside the concrete, while meeting the conductivity of the concrete and significantly enhancing the mechanical properties.

[0023] The steel fiber of this embodiment is also subjected to an impregnation treatment, and the specific impregnation method is as follows: The steel fiber and the impregnation liquid were ultrasonically impregnated at a weight ratio of 3:5, and after the impregnation was completed, the steel fiber was filtered and dried; The preparation method of the infiltration liquid is as follows: 2-5 parts of 5% by mass sodium silicate solution, 1-3 parts of silicon carbide whiskers, 3-5 parts of graphene and 3-5 parts of 4% by mass dopamine hydrochloride solution are fully mixed to obtain the infiltration liquid.

[0024] The ultrasonic power of the ultrasonic infiltration treatment in this embodiment is 400W, and the ultrasonic treatment is performed for 1 hour.

[0025] The method for preparing a high-performance conductive concrete with low carbon fiber content in this embodiment comprises the following steps: Step (1), pour cement, fly ash and silica fume into a mixer in sequence, and stir and mix them evenly to obtain a mixed dry material A; Step (2), pouring 60 wt% of the total required amount of water and a water reducing agent into a mixer, stirring and mixing to obtain a mixture B; Step (3) dispersing and dissolving the hydroxyethyl fiber with 40 wt% of water in a total required amount, and stirring with a glass rod to obtain a hydroxyethyl cellulose dispersion, and then pouring the chopped carbon fiber into the dispersion, and stirring with a glass rod until the carbon fiber is free of agglomeration, to obtain a carbon fiber dispersion; Step (4) adding the carbon fiber dispersion to the mixture B, and stirring and mixing to obtain a mixture C; Step (5) adding defoamer, river sand and steel fiber to mixture C in sequence and stirring and mixing to obtain conductive concrete slurry; Step (6) pouring the obtained slurry into a mold, vibrating it sufficiently, and placing it in a standard curing room for curing. After the curing is completed, high-performance conductive concrete with a low carbon fiber content can be obtained.

[0026] The stirring rate in step (1) of this embodiment is 62.5 r / min and the stirring time is 2 min; The stirring rate in step (2) is 62.5 r / min and the stirring time is 3 min; The stirring rate in step (4) is 62.5r / min and the stirring time is 4min; The stirring rate in step (5) is 62.5r / min and the stirring time is 5min; In step (3), a glass rod is used to manually stir for 1 minute to obtain a hydroxyethyl cellulose dispersion, and after adding carbon fiber, a glass rod is used to manually stir for 1 minute to obtain a carbon fiber dispersion.

[0027] In step (6) of this embodiment, the conductive concrete slurry is poured into the mold twice, and is vibrated after each pouring, with the total vibration time being no less than 1 minute; the curing conditions in the standard curing room are: the temperature is controlled at 20±2°C, and the humidity is greater than or equal to 95%.

[0028] Example 1: The high-performance conductive concrete with low carbon fiber content in this example is composed of the following components in parts by weight: 68 parts of cement, 25 parts of fly ash, 12 parts of silica fume, 20.5 parts of mixing water, 72.8 parts of river sand, 0.035 parts of chopped carbon fiber (0.03wt% of the mass of the cementitious material), 11.7 parts of steel fiber, 0.15 parts of hydroxyethyl cellulose, 0.315 parts of defoaming agent, and 1.575 parts of water reducing agent; wherein the cement model is P·O42.5 ordinary silicate cement; the river sand is standard river sand with a fineness modulus of 2.3-3.0 and a bulk density of 1560kg / m 3 ; The length of the chopped carbon fiber is 13mm, the diameter of the single fiber is 0.007mm, the tensile modulus is 23000MPA, and the density is 1.75g / cm 3; Steel fiber is copper-plated microfilament steel fiber, length 10-13mm, diameter 0.12mm, density 7800kg / m 3 The water reducer is a pure water-reducing type water reducer produced by Shanxi Feike New Material Technology Co., Ltd.; the defoamer is an organic phosphorus defoamer tributyl phosphate; the dispersant is hydroxyethyl cellulose; and the water is ordinary domestic water.

[0029] like Figure 1 As shown, the method for preparing high-performance conductive concrete with low carbon fiber content in this embodiment includes the following steps: Step (1), pouring 68 parts by weight of cement, 25 parts by weight of fly ash, and 12 parts by weight of silica fume into a mixer and stirring at a rate of 62.5 r / min for 2 minutes to obtain a mixed dry material A; Step (2), pouring 1.575 parts by weight of a water reducer and 12.3 parts by weight of water (60 wt% of the total required amount) into a mixer and stirring at a rate of 62.5 r / min for 3 min to obtain a mixture B; Step (3), 0.15 parts of dispersant and 8.2 parts of water (40 wt% of the total required amount) are poured into a beaker, and stirred manually using a glass rod for 1 minute to obtain a hydroxyethyl cellulose dispersion, and then 0.035 parts of chopped carbon fibers are added to the hydroxyethyl cellulose dispersion, and stirred using a glass rod for 1 minute, until the chopped carbon fibers have no obvious agglomeration phenomenon and the fibers are distinct, to obtain a carbon fiber dispersion; Step (4), pouring the chopped carbon fiber dispersion into a mixer in three equal amounts, and stirring the mixer at a rate of 62.5 r / min for 4 min to obtain a mixture C; Step (5), adding 0.315 parts by weight of a defoamer, 72.8 parts by weight of river sand, and 11.7 parts by weight of steel fiber into a mixer in sequence, and stirring the mixer at a rate of 62.5 r / min for 5 minutes to obtain a conductive concrete slurry; Step (6), pouring the conductive concrete slurry into the mold twice, vibrating it after each pouring, and the total vibration time is not less than 1 minute; the curing conditions in the standard curing room are: the temperature is controlled at 20±2°C, the humidity is greater than or equal to 95%, and it is taken out after curing to a specified age, so as to obtain high-performance conductive concrete with low carbon fiber content.

[0030] In order to test the high-performance conductive concrete with low carbon fiber content prepared in the example, the casting mold used in this example is a triple 40mm×40mm×160mm. Figure 2As shown, two brass meshes with a hole diameter of 4 mm were buried in the specimen as the electrodes of the specimen. The size was 30 mm × 60 mm, the interval between the copper meshes was 120 mm, and the distance between the copper meshes and the side end surface of the specimen was 20 mm. The test used the "double electrode method" AC power supply to measure the concrete resistivity. The calculation formula is shown in (1) (1) In formula (1), ρ is the resistivity of concrete, and its unit is ; R is the concrete resistance, unit is Ω, s is the area of ​​the electrode inserted into the concrete, unit is m 2 , L is the electrode distance in m.

[0031] Example 2: The components of the high-performance conductive concrete with low carbon fiber content in this example are different from those in Example 1 only in that the amount of chopped carbon fiber is 0.06wt% of the mass of the cementitious material, i.e., 0.07 parts by weight; and the amount of steel fiber is 7.8 parts by weight.

[0032] The preparation method of the high-performance conductive concrete with low carbon fiber content in this embodiment is the same as that in Embodiment 1, except that the amounts of added chopped carbon fibers and steel fibers are different.

[0033] The compressive strength and resistivity testing methods of the high-performance conductive concrete with low carbon fiber content in this embodiment are the same as those in Example 1.

[0034] Example 3: The components of the high-performance conductive concrete with low carbon fiber content in this example are different from those in Example 1 only in that the amount of chopped carbon fiber is 0.3wt% of the mass of the cementitious material, i.e., 0.35 parts by weight; and the amount of steel fiber is 7.8 parts by weight.

[0035] The preparation method of the high-performance conductive concrete with low carbon fiber content in this embodiment is the same as that in Embodiment 1, except that the amounts of added chopped carbon fibers and steel fibers are different.

[0036] The compressive strength and resistivity testing methods of the high-performance conductive concrete with low carbon fiber content in this embodiment are the same as those in Example 1.

[0037] Example 4: The components of the high-performance conductive concrete with low carbon fiber content in this example are different from those in Example 1 only in that the amount of chopped carbon fiber is 0.41 wt% of the mass of the cementitious material, i.e., 0.437 parts by weight.

[0038] The preparation method of the high-performance conductive concrete with low carbon fiber content in this embodiment is the same as that in Embodiment 1, except that the amount of added chopped carbon fibers is different.

[0039] The compressive strength and resistivity testing methods of the high-performance conductive concrete with low carbon fiber content in this embodiment are the same as those in Example 1.

[0040] The amounts of chopped carbon fibers and steel fibers used in Examples 1 to 4 are shown in Table 1: Table 1 Amount of chopped carbon fiber and steel fiber

[0041] After testing, the compressive strength, flexural strength and resistivity of the high-performance conductive concrete with low carbon fiber content in Examples 1 to 4 are shown in Table 2, Table 3 and Table 4 respectively: Table 2 Compressive strength of low carbon fiber high performance conductive concrete

[0042] Table 3 Flexural strength of low carbon fiber high performance conductive concrete

[0043] Table 4 Resistivity of low carbon fiber high performance conductive concrete

[0044] From Table 2, Table 3 and Table 4, it can be seen that the 7d resistivity of the concrete of the present invention can be less than 2.51 ,28d resistivity can reach 13.21 The compressive strength can reach 119.2MPA, and the flexural strength can reach 23.81MPA. The compressive strength and flexural strength of the concrete of the present invention can reach the best level of the prior art, and its resistivity can meet the requirements of snow and ice melting. The process is simple and does not require expensive equipment. Low production cost is achieved under low dosage conditions, and it is suitable for promotion and use.

[0045] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0046] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A high-performance conductive concrete with low carbon fiber content, characterized in that: The conductive concrete comprises the following raw materials in parts by weight: 66-68 parts of cement, 24-25 parts of fly ash, 10-12 parts of silica fume, 16.8-20.5 parts of mixing water, 70.2-72.8 parts of river sand, 0.035-0.437 parts of short-cut carbon fiber, 7.8-11.7 parts of steel fiber, 0.15-0.2 parts of hydroxyethyl cellulose, 0.315-0.42 parts of defoamer, 1.255-1.575 parts of water reducer and 35-40 parts of water; The steel fiber is also impregnated, and the specific impregnation method is: The steel fiber and the impregnation liquid are ultrasonically impregnated in a weight ratio of 3:5, and after the impregnation is completed, the impregnation is filtered and dried. The preparation method of the impregnation liquid is as follows: 2-5 parts of 5% by mass sodium silicate solution, 1-3 parts of silicon carbide whiskers and 3-5 parts of graphene and 3-5 parts of 4% by mass dopamine hydrochloride solution are fully mixed to obtain the impregnation liquid.

2. The high-performance conductive concrete with low carbon fiber content according to claim 1, characterized in that: The conductive concrete includes the following raw materials in parts by weight: 68 parts of cement, 25 parts of fly ash, 12 parts of silica fume, 20.5 parts of mixing water, 72.8 parts of river sand, 0.035 parts of short-cut carbon fiber, 11.7 parts of steel fiber, 0.15 parts of hydroxyethyl cellulose, 0.315 parts of defoaming agent, 1.575 parts of water reducing agent and 38 parts of water.

3. The high-performance conductive concrete with low carbon fiber content according to claim 1, characterized in that: The model of the cement is P·O42.5 ordinary Portland cement; the fly ash is secondary fly ash; the water reducing agent is polycarboxylic acid high-efficiency water reducing agent; the defoaming agent is organic phosphorus defoaming agent tributyl phosphate; and the water is ordinary domestic water.

4. The high-performance conductive concrete with low carbon fiber content according to claim 1, characterized in that: The river sand is standard river sand with a fineness modulus of 2.3-3.

0. The short-cut carbon fiber has a tensile strength of 4900Mpa, a tensile modulus of 230000MPA, a density of 1.75g / cm³, a fiber diameter of 0.007mm, and a bulk density of 0.4 g / cm 3 Resistivity 1.0-1.6 ×10 -1 ; The steel fiber is copper-plated microfilament steel fiber, with a length of 10-13mm, a diameter of 0.12mm, and a density of 7800kg / m 3 .

5. The high-performance conductive concrete with low carbon fiber content according to claim 1, characterized in that: The ultrasonic power of the ultrasonic infiltration treatment was 400 W, and the ultrasonic treatment lasted for 1 h.

6. A method for preparing high-performance conductive concrete with low carbon fiber content, characterized in that: The following steps are involved: Step (1), pour cement, fly ash and silica fume into a mixer in sequence, and stir and mix them evenly to obtain a mixed dry material A; Step (2), pouring 60 wt% of the total required amount of water and a water reducing agent into a mixer, stirring and mixing to obtain a mixture B; Step (3) dispersing and dissolving the hydroxyethyl fiber with 40 wt% of water in a total required amount, and stirring with a glass rod to obtain a hydroxyethyl cellulose dispersion, and then pouring the chopped carbon fiber into the dispersion, and stirring with a glass rod until the carbon fiber is free of agglomeration, to obtain a carbon fiber dispersion; Step (4) adding the carbon fiber dispersion to the mixture B, and stirring and mixing to obtain a mixture C; Step (5) adding defoamer, river sand and steel fiber to mixture C in sequence and stirring and mixing to obtain conductive concrete slurry; Step (6) pouring the obtained slurry into a mold, vibrating it sufficiently, and placing it in a standard curing room for curing. After the curing is completed, high-performance conductive concrete with a low carbon fiber content can be obtained.

7. The method for preparing high-performance conductive concrete with low carbon fiber content according to claim 6, characterized in that: The stirring rate in step (1) is 62.5 r / min and the stirring time is 2 min; The stirring rate in step (2) is 62.5 r / min and the stirring time is 3 min; The stirring rate in step (4) is 62.5r / min and the stirring time is 4min; The stirring rate in step (5) is 62.5r / min and the stirring time is 5min; In step (3), a glass rod is used to manually stir for 1 minute to obtain a hydroxyethyl cellulose dispersion, and after adding carbon fiber, a glass rod is used to manually stir for 1 minute to obtain a carbon fiber dispersion.

8. The method for preparing high-performance conductive concrete with low carbon fiber content according to claim 7, characterized in that: Step (6) The conductive concrete slurry is poured into the mold in two times, and vibrated after each pouring, and the total vibration time is not less than 1 minute; the curing conditions of the standard curing room are: the temperature is controlled at 20±2°C, and the humidity is greater than or equal to 95%.

Citation Information

Patent Citations

  • Iron tailing large-slump high-strength conductive concrete and preparation method thereof

    CN112521076A

  • Conducting concrete, manufacturing method thereof and application

    CN106495607A

  • High-strength recycled concrete and preparation method thereof

    CN113354369A

  • High-conductivity composite grounding material and preparation method thereof

    CN113816697A

Cited By

  • Conductive fiber reinforced concrete and preparation method thereof

    CN120365013A

  • Low-carbon conductive concrete and preparation method thereof

    CN120647278A